Adsorptive desulfurization of model diesel fuel using activated clay (AC) batch and column studies - Antonio, Rheamay V. (College of Engineering, University of the Philippines Diliman, 2014)
Sulfur in transportation fuel is a major source of air pollution. During combustion, sulfur in diesel can be converted into sulfur oxide and sulfate particulate matters. In this study, the removal of dibenzothiophene sulfone (DBTO) from model diesel fuel was investigated using activated clay (AC) as natural adsorbent. The effects of reaction temperature, dosage, agitation speed and initial sulfur concentration on sulfur removal were investigated. Results from the batch experiments showed that sulfur removal increased with contact time, reaction temperature, agitation speed and adsorbent dosage. The adsorptive desulfurization used in this study was able to lower the initial sulfur concentration of 500 to 30 ppm. It was also found out that experimental data followed the Languir isotherm (R2 = 0.9994) and the pseudo second kinetic model (R2 = 0.99999) at 30°C. Thermodynamic studies proved that the adsorption process was spontaneous (ΔG -6.44) and favorable. In addition results from the column study showed that flow rate, influent concentration and bed height affect the breakthrough curves. A maximum sulfur adsorption capacity of 4.65 mg DBTO/g of AC was obtained. The present study demonstrates that AC is an effective adsorbent for the removal of DBTO from model diesel fuel.